SARS-CoV-2-related MIS-C: A key to the viral and genetic causes of Kawasaki disease? - Sancho-Shimizu, Vanessa; Brodin, Petter; Cobat, Aurelie; Biggs, Catherine M; Toubiana, Julie; Lucas, Carrie L; Henrickson, Sarah E; Belot, Alexandre; Tangye, Stuart G; Milner, Joshua D; Levin, Michael; Abel, Laurent; et al. (J Exp Med, 2021)
Multisystem inflammatory syndrome in children (MIS-C) emerged in April 2020 in communities with high COVID-19 rates. This new condition is heterogenous but resembles Kawasaki disease (KD), a well-known but poorly understood and clinically heterogenous pediatric inflammatory condition for which weak associations have been found with a myriad of viral illnesses. Epidemiological data clearly indicate that SARS-CoV-2 is the trigger for MIS-C, which typically occurs about 1 mo after infection. These findings support the hypothesis of viral triggers for the various forms of classic KD. We further suggest that rare inborn errors of immunity (IEIs) altering the immune response to SARS-CoV-2 may underlie the pathogenesis of MIS-C in some children. The discovery of monogenic IEIs underlying MIS-C would shed light on its pathogenesis, paving the way for a new genetic approach to classic KD, revisited as a heterogeneous collection of IEIs to viruses.
Keywords: Biomarkers; Child; COVID-19; Cytokines; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inflammation; Inflammation Mediators; Lymphohistiocytosis, Hemophagocytic; Models, Biological; Mucocutaneous Lymph Node Syndrome; Pandemics; SARS-CoV-2; Systemic Inflammatory Response Syndrome